Dynamic prediction in breast cancer: proving feasibility in clinical practice using the TEAM trial. (10th April 2015) - Fontein, D. B. Y.; Klinten Grand, M.; Nortier, J. W. R.; Seynaeve, C.; Meershoek-Klein Kranenbarg, E.; Dirix, L. Y.; van de Velde, C. J. H.; Putter, H.
Abstract : Predictive models are an integral part of clinical practice and help determine optimal treatment strategies for individual patients. We present a novel technique that enables a more individualized prediction of 5-year overall survival in individual patients during adjuvant endocrine therapy (ET). Our nomogram facilitates in determining whether further ET will benefit an individual patient. Abstract: Background: Predictive models are an integral part of current clinical practice and help determine optimal treatment strategies for individual patients. A drawback is that covariates are assumed to have constant effects on overall survival (OS), when in fact, these effects may change during follow-up (FU). Furthermore, breast cancer (BC) patients may experience events that alter their prognosis from that time onwards. We investigated the 'dynamic' effects of different covariates on OS and developed a nomogram to calculate 5-year dynamic OS (DOS) probability at different prediction timepoints ( t P ) during FU. Methods: Dutch and Belgian postmenopausal, endocrine-sensitive, early BC patients enrolled in the TEAM trial were included. We assessed time-varying effects of specific covariates and obtained 5-year DOS predictions using a proportional baselines landmark supermodel. Covariates included age, histological grade, hormone receptor and HER2 status, T- and N-stage, locoregional recurrence (LRR), distant recurrence, and treatment compliance. A nomogram was designed to calculate 5-year DOS based on individual characteristics. Results: A total of 2602 patients were included (mean FU 6.2 years). N-stage, LRR, and HER2 status demonstrated time-varying effects on 5-year DOS. Hazard ratio (HR) functions for LRR, high-risk N-stage (N2/3), and HER2 positivity were HR = (8.427 × 0.583  t P ), HR = (3.621 × 0.816  t P ), and HR = (1.235 × 0.851  t P ), respectively. Treatment discontinuation was associated with a higher mortality risk, but without a time-varying effect [HR 1.263 (0.867–1.841)]. All other covariates were time-constant. Discussion: The current nomogram accounts for elapsed time since starting adjuvant endocrine treatment and optimizes prediction of individual 5-year DOS during FU for postmenopausal, endocrine-sensitive BC patients. The nomogram can facilitate in determining whether further therapy will benefit an individual patient, although validation in an independent dataset is still needed.